Application of the Simple Additive Weighting (SAW) Method in Recommended Skripsi Topics - Tengsi Mayang Nopita Sari; Liza Yulianti; Devi Sartika (Penerbit Jurnal Indonesia, 2022)
Students were confused by the selection of thesis topics from the 3 thesis topics to be discussed in research, thus slowing down the thesis submission process and some students did not submit titles during semester 7. thesis topic, one way is by utilizing information technology systems. The recommendation application for thesis topics at the Management Study Program, Faculty of Economics, University of Dehasen Bengkulu, was made using the Visual Basic .Net programming language and SQL Server 2008r2 database. In the application, one of the Decision Support System (DSS) methods has been applied, namely the Simple Additive Weighting (SAW) method which is used to help determine recommendations for final semester student thesis topics based on the value of the courses obtained by students. There are 3 thesis topics in the Management Study Program, Faculty of Economics, University of Dehasen Bengkulu, namely finance, human resources, and marketing with a course value of 17 courses. Recommendations for this thesis topic are given per student by generating course grades for each student. Based on the results of the black box test, the functional application of the thesis topic recommendation at the Management Study Program, Faculty of Economics, Dehasen Bengkulu University has been running properly and is able to display the results of the thesis topic recommendation for each student through the stages of the SAW method.